(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article reveals the importance of the Uzbek language today. The issues of its digitization and use in conjunction with artificial intelligence tools are analyzed using world experience and national research. Specific proposals are made to solve existing problems in this regard. This article serves as a basis for further research on the development of the Uzbek language.